Akses Keluarga Pra Sejahtera dalam Memenuhi Kebutuhan Dasar Kesehatan: Studi di Dusun Kedung Dendeng Jipurapah Jombang - Ahmad Faqih; Sugeng Harianto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the socio-economic conditions of underprivileged families and the barriers to accessing healthcare services in Kedungdendeng Hamlet, Jipurapah Village, Plandaan District, Jombang Regency. This study employed a qualitative research method with a descriptive-analytical approach. Data were collected through in-depth interviews with twelve informants, field observations, and documentation studies. Data analysis was conducted using the interactive model developed by Miles and Huberman (1994), while the analytical framework was based on Anthony Giddens’ Structuration Theory, particularly the concepts of the duality of structure, agency, practical consciousness, and unintended consequences of action. The findings reveal that poverty in Kedungdendeng Hamlet is multidimensional and structural in nature. Residents rely primarily on seasonal agriculture and profit-sharing livestock farming, characterized by unstable incomes and weak bargaining positions due to the dominance of middlemen. The hilly geographical conditions and limited road infrastructure constitute major barriers to accessing healthcare services. No healthcare facilities are available in Jipurapah Village, visits from community health center personnel are limited, and the National Health Insurance (JKN/KIS) program has not functioned optimally due to administrative constraints and transportation costs. Cultural barriers, including a curative-oriented perspective on health, reliance on traditional medicine, and low levels of health literacy, further exacerbate the situation. In response, residents have developed adaptive strategies based on social capital, such as mutual cooperation emergency stretcher systems, medicine-sharing networks, and traditional treatment practices. Giddens’ analysis demonstrates the duality of structure between structural constraints and social solidarity as an enabling force. However, these informal adaptation strategies simultaneously reproduce the absence of formal support systems. This study confirms that poverty is a product of structural conditions that require systemic and comprehensive interventions.